Business model innovation by design: a review of design's role in business model innovation. Issue 2 (2nd April 2020) - Bryant, Scott T.; Straker, Karla; Wrigley, Cara
ABSTRACT: In recent years, design research has increasingly focused on its use in the business model and innovation space. Despite this increased, little clarity exists surrounding the contribution of design in facilitating business model innovation outcomes. A literature review was conducted to answer the question: how does design contribute to business model innovation outcomes? 316 design and business model innovation (BMI) focused papers were reviewed, identifying five categories of design and BMI: functional design, outcome-based design, design as a methodology, design-logic orientation, and non-design. Reflection upon these 316 papers also highlighted a lack of repeatability and standardization amongst papers using design approaches to achieve BMI. This suggested a need to develop a clear, replicable design approach to achieving BMI outcomes in order to allow for the research field to build a consistent and rigorous evidence-base. Therefore, four meta-archetypes were identified for use as a first step toward building a consistent body of evidence for the contribution of design to BMI outcomes. The process describes the role of design in BMI processes, linking abstract and often external concepts, to tangible alternative business models – all in pursuit of better serving end-user needs and providing practitioners with replicable, transparent approaches to design and BMI.